Diversity of Cellulolytic Microbes from Several Depth in Peat Soil Planted with Oil Palm (Journal of Wetlands Environmental Management, 2024)
Present research was carried out to elucidate the diversity diversity of cellulolytic microbes from several depth in peat soil planted with oil palm. Soil samples were taken from wetlands cultivated to 2 years, 6 years, and 10 years old oil palm, as well as secondary forest, in Landasan Ulin Utara village, South Kalimantan. Soil samples were transported to the laboratory and used for determination of population of cellulolytic microbes, microbial C, soil pH, and water content. Correlation test was employed to assess the relationship between population of cellulolytic decomposer with microbial C, soil pH, and water content. The results showed that the largest cellulolytic bacterial population was found at a depth of 0-40 cm from 10 years old oil palms, followed by a depth of >40 cm from 10 years old oil palms. There was no difference between cellulolytic bacterial populations from 6 and 2 years old palms at all depths. The lowest population of cellulolytic bacteria was found at a depth of >40 cm from forest soil. There were positive correlations between population of cellulotic decomposer with all parameter measured, except soil water content that were logistic negatively correlated. The relationship between water content (Y, mm/day) and the population of cellulolytic decomposer (x, cfu/g soil) can be described with equation Y = log (-0.0051x + 162.65). These findings suggested that the organic matters supplied by oil palm, especially the 10 years old oil palm) enhance the diversity of cellulolytic microbes. These results may also suggest that the cellulolytic microbes were mostly from aerobic type.